Effects of Project-Related and Organizational-Related Factors on Five Dimensions of Project Performance: A Study Across the Construction Sectors in Malaysia. Issue 4 (2nd October 2018) - Sekar, Gopal; Viswanathan, Kuperan; Sambasivan, Murali
Abstract: The objective of this research is to analyze the relationships of project-related and organizational-related factors with five dimensions of project performance across different sectors of the construction industry. Data collected from the project managers and directors of 360 construction firms in Malaysia were analyzed using multiple-regression technique with size of the organization as a control variable. The important finding is that the effects of project-related and organizational-related factors differ by sector type and by dimensions of project performance. The findings of this study can help project managers devise and implement appropriate strategies to support project success.